Induction of autotetraploidy using colchicine and its identification in radish (Raphanus sativus L.). Issue 1 (2nd January 2016) - Limera, C.; Wang, K.; Xu, L.; Wang, Y.; Zhu, X.; Feng, H.; Sha, Y.; Gong, Y.; Liu, L.
ABSTRACT: Radish ( Raphanus sativus L.) is an important root vegetable in the family Brassicaceae, and is popular worldwide, especially in East Asia. Colchicine was used to induce autotetraploidy in four advanced inbred lines of radish. A combination of 0.1% (w/v) colchicine in 0, 0.1%, 0.2%, or 0.4% (v/v) dimethyl sulphoxide (DMSO) was applied to the apical meristem of young seedlings. A preliminary screening for putative tetraploids was conducted based on morphological traits including flower size, the number of chloroplasts in guard cells, stomatal size, and stomatal density. Plants with significantly larger stomata, with more chloroplasts in their guard cells, were selected for further analysis by chromosome counting. Only one tetraploid genotype, 'Nau-dy13', was successfully induced using 0.1% (w/v) colchicine plus 0.2% (v/v) DMSO, with a tetraploid induction rate of 20%. Application of the above concentrations of colchicine and DMSO to the apical meristem of 'Nau-dy13' seedlings was found to be an efficient method to induce polyploidy in radish. The tetraploid plants had larger flowers, stomata, and pollen grains and a chromosome number of 4x = 36. In contrast, the rate of pollen germination (19.24%) in the tetraploid genotype was lower than in the diploid line (55.80%). Levels of expression of six genes controlling meiosis, MER3/RCK, ATK1, ATK5, DMC1, TTN8, and MPS1, were measured using real-time reverse transcription quantitative PCR (RT-qPCR). Expression of MPS1 was downregulated 0.6-fold in autotetraploid plants compared to diploid plants. An efficient method for the induction of tetraploids in radish has been established. This will facilitate the manipulation of ploidy level when developing novel elite germplasm and allow further analysis of the mechanism of polyploidy in radish.